2006
DOI: 10.1111/j.1468-2982.2005.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Fibromyalgia Syndrome in Migraine Patients

Abstract: Fibromyalgia syndrome (FMS) is a chronic pain syndrome of unknown aetiology characterized by diffuse pain over more than 3 months and tenderness in specific sites named tender points. The aim of this study was to assess the prevalence and severity of FMS among patients suffering from episodic migraine. Ninety-two consecutive patients (20 male, 72 female) fulfilling the International Headache Society criteria for migraine with and without aura from a tertiary headache clinic were evaluated. A headache and gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
73
0
8

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 25 publications
14
73
0
8
Order By: Relevance
“…The magnitude of this association increased with the frequency of headache, with individuals who experience headaches on 15 or more days per month (women: OR=5.3; 95%CI: 4.4-6.5 while men OR=3.6; 95%CI: 2.9-4.5). Furthermore, a high prevalence of fibromyalgia has been found among subjects with migraine [74,75].This increased odds of having co-morbid musculoskeletal pain when diagnosed with migraine was also observed among children and young adults. In a cross-sectional population-based study, including over 9000 adolescents and young adults revealed a strong association between headache felt more than 30 days per year and frequent low back pain (OR=3.4; 95%CI: 2.3-5.0) [76].…”
mentioning
confidence: 78%
See 2 more Smart Citations
“…The magnitude of this association increased with the frequency of headache, with individuals who experience headaches on 15 or more days per month (women: OR=5.3; 95%CI: 4.4-6.5 while men OR=3.6; 95%CI: 2.9-4.5). Furthermore, a high prevalence of fibromyalgia has been found among subjects with migraine [74,75].This increased odds of having co-morbid musculoskeletal pain when diagnosed with migraine was also observed among children and young adults. In a cross-sectional population-based study, including over 9000 adolescents and young adults revealed a strong association between headache felt more than 30 days per year and frequent low back pain (OR=3.4; 95%CI: 2.3-5.0) [76].…”
mentioning
confidence: 78%
“…The magnitude of this association increased with the frequency of headache, with individuals who experience headaches on 15 or more days per month (women: OR=5.3; 95%CI: 4.4-6.5 while men OR=3.6; 95%CI: 2.9-4.5). Furthermore, a high prevalence of fibromyalgia has been found among subjects with migraine [74,75].…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Ifergane et al (16) reported that, FMS was found in 22% percent of female patients with migraine and, patients suffering from migraine-FMS had lower quality of life scores and higher levels of mental distress. Kozanoğlu et al (17) showed that the prevalence of FMS was 18.9% in patients with hepatitis C infection.…”
Section: Discussionmentioning
confidence: 99%
“…7,27 In addition, a large number of diseases have been associated with migraine, including fibromyalgia, 28 depression, 29 sleep disorders, 30,31 and other disturbances of movement mediated by dopaminergic pathways. 32,33 These associations suggest that migraine may share physiopathological aspects with other diseases, stimulating the investigation of these comorbidities.…”
mentioning
confidence: 99%